Isocyanate-modified pitch-based hard carbon material and method for producing the same

CN122977362APending Publication Date: 2026-10-27XINJIANG UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611367418.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]为了解决现有技术中沥青基硬碳材料电化学性能不够理想,制备工艺繁复,碳利用率不高的缺陷

Benefits of technology

[0024](1)本发明利用异氰酸酯与羟基之间的反应,在固相条件下构建交联结构,减少或避免溶剂使用,工艺简单。(2)本发明采用低升温速率含氧预氧化,使前驱体在熔融流动前充分氧化交联,得到不粘壁、不结块的前驱体,有利于连续化和规模化生产。(3)本发明将沥青与异氰酸酯和含羟基廉价碳源复合,能够兼顾高产碳率、结构无序化和储钠活性位点构建。(4)本发明优选技术方案中,采用小分子二异氰酸酯和异氰酸酯多聚体的复配,可以实现硬碳材料的多项电化学性能的改善。(5)本发明不需要必须引入金属盐、强酸、硫源或复杂模板剂,原料体系简单,后处理压力小。(6)由本发明方法制得的硬碳材料可用于钠离子电池负极,具有较高首次库仑效率和较高可逆容量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977362A_ABST
    Figure CN122977362A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of hard carbon materials, in particular to an isocyanate modified asphalt-based hard carbon material and a preparation method thereof. The preparation method of the isocyanate modified asphalt-based hard carbon material comprises the following steps: (S1) uniformly mixing asphalt, an isocyanate crosslinking agent and polysaccharide; (S2) allowing the mixture to stand and react, so that the isocyanate reacts with the hydroxyl group to obtain a crosslinking precursor; (S3) pre-oxidizing the crosslinking precursor in an oxygen-containing atmosphere; (S4) pre-carbonizing in an inert atmosphere, and then high-temperature carbonizing to obtain the hard carbon material. The electrochemical performance of the hard carbon material prepared by the preparation method is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hard carbon materials technology, and in particular to an isocyanate-modified pitch-based hard carbon material and its preparation method. Background Technology

[0002] Sodium-ion batteries, with their advantages of abundant sodium resources, low cost, and good safety, are considered an important rechargeable battery system suitable for large-scale energy storage. In sodium-ion battery systems, battery capacity, initial coulombic efficiency, rate performance, and cycle life have a significant impact on the anode material. Hard carbon materials, due to their large interlayer spacing, disordered carbon structure, and good sodium storage capacity, are considered one of the most promising anode materials for sodium-ion batteries in terms of practical application.

[0003] Asphalt-based materials have advantages such as wide availability, low cost, and high carbon yield, making them important precursors for preparing carbon materials for sodium-ion battery anodes. However, asphalt is prone to softening and melting during heat treatment, forming a relatively ordered soft carbon structure, resulting in low reversible capacity and poor rate performance of the obtained carbon materials. CN121849911A discloses an asphalt-based hard carbon and its preparation method. This patent points out that asphalt has high yield, low cost, and high carbon yield, but carbon materials prepared from asphalt tend to exhibit soft carbon properties, resulting in low reversible capacity and poor rate performance. The solution is to mix the asphalt precursor, sulfur source, and crosslinking agent, then perform crosslinking and vulcanization treatment, followed by carbonization treatment, to improve the reversible capacity and rate performance of the asphalt-based hard carbon.

[0004] In summary, existing technologies have improved the performance of hard carbon materials by focusing on carboxyl group regulation, sulfur source crosslinking, coal-based oxidative crosslinking, and biomass / asphalt composites. However, the following problems still exist: First, it requires the introduction of sulfur sources, metal salts, nano-oxides, boron nitride nanosheets, or acid washing, which makes the process complex and increases costs and post-processing pressure. Second, existing methods do not fully utilize the solid-phase crosslinking effect between asphalt and crosslinking agents, making it difficult to simultaneously achieve precursor melt resistance stability, hard carbon structure regulation, first coulombic efficiency, and reversible capacity under simple processes.

[0005] Existing reports on isocyanate crosslinking modification of asphalt-based carbon sources are mostly for road asphalt materials, aiming to improve the mechanical properties of pavement asphalt materials, such as low-temperature crack resistance and high-temperature rutting resistance. The inventors previously attempted to prepare hard carbon materials by combining asphalt and isocyanate crosslinking agents, but the results were not ideal, and the improvement in the resulting hard carbon materials was not significant. This may be because isocyanates require reaction with active hydrogen to form a crosslinked structure, while asphalt's main components are polycyclic aromatic hydrocarbons with a low active hydrogen content. Therefore, directly combining asphalt and isocyanate to prepare hard carbon materials cannot effectively inhibit graphitization during the carbonization process, nor can it effectively construct a closed-cell structure. Summary of the Invention

[0006] To address the shortcomings of existing pitch-based hard carbon materials, such as unsatisfactory electrochemical performance, complex preparation processes, and low carbon utilization, this invention aims to provide an isocyanate-modified pitch-based hard carbon material for sodium-ion batteries, its preparation method, and its applications. This invention provides a method for preparing hard carbon materials that utilizes widely available raw materials, employs a simple process suitable for solid-state operation, effectively avoids adhesion and agglomeration of pitch-based or other hydroxyl-containing carbon precursors during heat treatment, and simultaneously improves the performance of the anode in sodium-ion batteries. This method should achieve synergistic optimization of the hard carbon material's structure and electrochemical performance through crosslinking reactions between hydroxyl-containing carbon precursors, isocyanate crosslinking agents, and inexpensive hydroxyl-containing carbon sources, combined with low-rate pre-oxidation and high-temperature carbonization. This solves the problems of difficulty in controlling the structure of the resulting hard carbon material and the challenge of simultaneously achieving optimal initial coulombic efficiency and reversible capacity.

[0007] To achieve the above objectives, the present invention first provides a method for preparing isocyanate-modified pitch-based hard carbon materials, comprising the following steps:

[0008] (S1) Mix the asphalt, isocyanate crosslinking agent and polysaccharide evenly;

[0009] (S2) Allow the mixture to stand and react, allowing the isocyanate to react with the hydroxyl groups to obtain the crosslinking precursor;

[0010] (S3) Pre-oxidize the crosslinking precursor in an oxygen-containing atmosphere;

[0011] (S4) Pre-carbonize in an inert atmosphere and then carbonize at high temperature to obtain hard carbon material.

[0012] Further, in step S1, the asphalt is selected from at least one of coal tar pitch and petroleum asphalt, and softened at 60-180℃; the isocyanate crosslinking agent is selected from toluene diisocyanate, diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, triphenylmethane triisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, HDI trimer, IPDI trimer, and polymeric MDI; the polysaccharide is selected from at least one of sucrose, starch, cellulose and its derivatives, chitosan, and dextran.

[0013] Furthermore, the isocyanate crosslinking agent is a mixture of small-molecule diisocyanate and isocyanate polymers; the small-molecule diisocyanate is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, triphenylmethane triisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate; the isocyanate polymer is selected from at least one of HDI trimer, IPDI trimer, and polymeric MDI; and the polysaccharide is sucrose. The inventors have discovered that by selecting the above-mentioned specific isocyanate crosslinking agent and sucrose, the resulting hard carbon material exhibits optimal electrochemical performance, with simultaneous improvements in capacity, initial coulombic efficiency, and rate performance. Compared to small-molecule diisocyanates, isocyanate polymers have higher molecular weights and greater functionality, enabling them to provide more complex cross-linking networks. High-temperature carbonization effectively inhibits the graphitization of asphalt molecules and promotes the formation of closed pores, increasing capacity. Small-molecule diisocyanates, with their strong mobility and high reactivity, can quickly penetrate into the interior of macromolecules such as asphaltene, reacting with deep active sites (such as hydroxyl groups) to form uniform initial cross-linking points. The synergistic effect of small-molecule diisocyanates and isocyanate polymers forms a uniform and abundant cross-linking network. The inventors also speculate that this synergistic effect lies in the fact that the two work together to form a structure that balances rigidity and toughness. The polymers can form cross-linking points with high rigidity and thermal stability, while the connecting segments formed by small-molecule diisocyanates can provide a certain buffer between the rigid networks, helping to alleviate the internal stress caused by volume shrinkage during carbonization, preventing material cracking, maintaining structural integrity, and further improving long-cycle performance.

[0014] Preferably, the isocyanate crosslinking agent is a mixture of small molecule diisocyanate and isocyanate polymer in a mass ratio of 1-2:1.

[0015] The preferred polysaccharide is sucrose, primarily because it is inexpensive and readily available, contains a large number of hydroxyl groups, and can react with isocyanates to form a stable chemical cross-linking network, improving the material's stability and electrochemical performance. Furthermore, sucrose decomposes during heating to produce gases; through a pre-carbonization process, these gases are contained within the cross-linked carbon layers, forming a closed-cell structure crucial for sodium storage and providing low-voltage plateau capacity.

[0016] Further, in step S1, the mass ratio of asphalt, isocyanate crosslinking agent and polysaccharide is 4-6:2-3:1-2; the mixing is not particularly limited, such as ball milling, grinding, high-speed mixer, or double planetary mixer.

[0017] Furthermore, in step S2, the static reaction is allowed to stand at 15-40°C for 3-6 hours.

[0018] Further, in step S3, the oxygen-containing atmosphere is oxygen or air, and the pre-oxidation involves heating to 250-300℃ and holding at that temperature for 1-2 hours; the heating rate is 0.1-2℃ / min, preferably 0.5-1℃ / min. In step S2, the pre-oxidation uses a lower heating rate to ensure that the precursor undergoes sufficient oxidative cross-linking before softening or melting, thereby obtaining a pre-oxidized precursor that does not stick to the wall or clump.

[0019] Further, in step S4, the inert atmosphere is nitrogen and / or argon, and the pre-carbonization is to heat to 400-500℃, preferably 450℃, and hold for 3-6 hours, with a heating rate of 1-20℃ / min, such as 2-5℃ / min; the high-temperature carbonization is to heat to 1000-1400℃ and hold for 4-8 hours.

[0020] The present invention also provides a sodium-ion battery hard carbon material, which is prepared by the above-described preparation method.

[0021] This invention also provides the use of the hard carbon material prepared by the above method as a negative electrode material for sodium-ion batteries.

[0022] The present invention also provides a sodium-ion battery, wherein the negative electrode comprises the hard carbon material prepared by the above preparation method.

[0023] Compared with the prior art, the present invention achieves the following beneficial effects:

[0024] (1) This invention utilizes the reaction between isocyanate and hydroxyl groups to construct a cross-linked structure under solid-phase conditions, reducing or avoiding the use of solvents, and the process is simple. (2) This invention uses oxygen-containing pre-oxidation at a low heating rate to fully oxidize and cross-link the precursor before it melts and flows, resulting in a precursor that does not stick to the wall or clump, which is beneficial for continuous and large-scale production. (3) This invention combines asphalt with isocyanate and a cheap carbon source containing hydroxyl groups, which can simultaneously achieve high carbon yield, structural disorder, and the construction of sodium storage active sites. (4) In the preferred technical solution of this invention, the combination of small molecule diisocyanate and isocyanate polymers can improve multiple electrochemical properties of hard carbon materials. (5) This invention does not require the introduction of metal salts, strong acids, sulfur sources, or complex template agents, the raw material system is simple, and the post-processing pressure is low. (6) The hard carbon material prepared by the method of this invention can be used as the negative electrode of sodium-ion batteries, with high initial coulombic efficiency and high reversible capacity. Attached Figure Description

[0025] Figure 1 The thermogravimetric curve of the pre-oxidized precursor obtained in step S3 of Example 1 under a nitrogen-carrying atmosphere is shown.

[0026] Figure 2 These are the infrared spectra of the pre-oxidized precursor and the direct pre-oxidized asphalt obtained in Example 1.

[0027] Figure 3 This is a SEM image of the hard carbon material obtained in Example 1 of the present invention. Detailed Implementation

[0028] The present invention will now be described with reference to specific embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the invention. Conventional adjustments made by those skilled in the art to the types and proportions of raw materials, temperature, time, atmosphere, and heating rate without departing from the concept of the invention should be included within the scope of protection of the present invention.

[0029] Example 1

[0030] (S1) Weigh 6 kg of coal tar pitch (softening point 135℃), 3 kg of polymeric MDI (PM200) and 2 kg of sucrose, and mix them in a scraper mixer to obtain a mixture;

[0031] (S2) The mixture was placed in a sealed container and allowed to stand at room temperature (25±1℃) for 3 hours. The resulting material was then thoroughly ground to obtain the crosslinking precursor.

[0032] (S3) The crosslinking precursor is placed in a tube furnace filled with oxygen and heated to 300°C at a heating rate of 0.5°C / min. The temperature is held for 1 hour to obtain the pre-oxidized precursor. Figure 1 The thermogravimetric analysis (TGA) diagram of the pre-oxidized precursor obtained in Example 1 under a nitrogen atmosphere shows that the pre-oxidized precursor has a small weight loss below 300°C, with the main weight loss occurring at approximately 350–500°C. It still has a high char residue at high temperatures, indicating that it has good thermal stability. Figure 2 The images show the infrared spectra of the pre-oxidized precursor obtained in Example 1 and the direct pre-oxidized asphalt. It can be seen that the pre-oxidized precursor in Example 1 exhibits obvious characteristic absorptions such as C=O, NH / CN, and CN / CO, and the CO / COC region shows significant changes, indicating that the isocyanate reacts with the hydroxyl-containing component to form a cross-linked structure.

[0033] (S4) The pre-oxidized precursor is transferred to a tube furnace with argon gas and heated to 450°C at a heating rate of 2°C / min. The temperature is held for 4 hours to obtain the pre-carbonized precursor. The pre-carbonized precursor is further heated to 1300°C in an argon atmosphere and held for 4 hours. After naturally cooling to room temperature, the hard carbon material (called HCl) is obtained.

[0034] Figure 3 This is a SEM image of the hard carbon material obtained in Example 1. In addition to crosslinking, nitrogen doping of isocyanate can also suppress the stacking of carbon layers and particle agglomeration during high-temperature carbonization.

[0035] Example 2

[0036] (S1) Weigh 4 kg of coal tar pitch (softening point 135℃), 2 kg of polymeric MDI (PM200) and 1 kg of sucrose, and mix them in a scraper mixer to obtain a mixture;

[0037] (S2) The mixture was placed in a sealed container and allowed to stand at room temperature (25±1℃) for 3 hours. The resulting material was then thoroughly ground to obtain the crosslinking precursor.

[0038] (S3) The crosslinking precursor is placed in a tube furnace filled with oxygen and heated to 250°C at a heating rate of 0.5°C / min. The temperature is held for 1 hour to obtain the pre-oxidized precursor.

[0039] (S4) The pre-oxidized precursor is transferred to a tube furnace with argon gas and heated to 400°C at a heating rate of 2°C / min. The temperature is held for 4 hours to obtain the pre-carbonized precursor. The pre-carbonized precursor is further heated to 1300°C in an argon atmosphere and held for 4 hours. After naturally cooling to room temperature, the hard carbon material (called HC2) is obtained.

[0040] Example 3

[0041] (S1) Weigh 5 kg of coal tar pitch (softening point 135℃), 2 kg of polymeric MDI (PM200) and 2 kg of sucrose, and mix them in a scraper mixer to obtain a mixture;

[0042] (S2) The mixture was placed in a sealed container and allowed to stand at room temperature (25±1℃) for 3 hours. The resulting material was then thoroughly ground to obtain the crosslinking precursor.

[0043] (S3) The crosslinking precursor is placed in a tube furnace filled with oxygen and heated to 300°C at a heating rate of 0.5°C / min. The temperature is held for 1 hour to obtain the pre-oxidized precursor.

[0044] (S4) The pre-oxidized precursor is transferred to a tube furnace with argon gas and heated to 500°C at a heating rate of 2°C / min. The temperature is held for 4 hours to obtain the pre-carbonized precursor. The pre-carbonized precursor is further heated to 1300°C in an argon atmosphere and held for 4 hours. After naturally cooling to room temperature, the hard carbon material is obtained.

[0045] Example 4

[0046] The other conditions are the same as in Example 1, except that the isocyanate crosslinking agent is replaced with 3 kg of toluene diisocyanate.

[0047] Example 5

[0048] The other conditions are the same as in Example 1, except that the isocyanate crosslinking agent is replaced with 1.5 kg of toluene diisocyanate and 1.5 kg of polymeric MDI.

[0049] Example 6

[0050] The other conditions are the same as in Example 1, except that the isocyanate crosslinking agent is replaced with 2 kg of toluene diisocyanate and 1 kg of polymeric MDI.

[0051] Example 7

[0052] The other conditions are the same as in Example 1, except that the isocyanate crosslinking agent is replaced with 2 kg of diphenylmethane diisocyanate and 1 kg of HDI trimer.

[0053] Comparative Example 1

[0054] Steps S1 to S3 are the same as in Example 1.

[0055] (S4) The pre-oxidized precursor is transferred to a tube furnace purged with argon gas and heated to 1300°C at a heating rate of 2°C / min. The temperature is held for 6 hours and then naturally cooled to room temperature to obtain hard carbon material (referred to as HC3). That is, compared with Example 1, no pre-carbonization is performed.

[0056] Comparative Example 2

[0057] The other conditions are the same as in Example 1, except that sucrose is not added in step S1.

[0058] Comparative Example 3

[0059] The other conditions are the same as in Example 1, except that in step S1, the isocyanate crosslinking agent is replaced with an equal mass of bisphenol A epoxy resin (E-20).

[0060] Application examples

[0061] The hard carbon material, conductive additive SP, and binder CMC / SBR obtained in the above examples and comparative examples were mixed at a weight ratio of 93:3:4, dissolved in water, and stirred to obtain a uniform slurry. The slurry was then uniformly coated onto carbon-coated aluminum foil using a 75μm scraper, dried, and sliced ​​to obtain the negative electrode sheet.

[0062] The dried negative electrode sheet was assembled into a coin cell with a sodium metal negative electrode, a carboxylic acid cellulose separator, and an EC / DMC / EMC / 1M NaPF6 electrolyte (EC / DMC / EMC = 1:1:1, volume ratio). The cell was then placed on the LAND test platform for testing, and the first cycle curve is shown in Table 1. Figure 3 The charging and discharging curves of the hard carbon materials obtained in Examples 1, 2, and 1 of this invention are shown.

[0063] The electrochemical performance of the negative electrode materials obtained in the above embodiments and comparative examples is listed in Table 1 below:

[0064] Table 1 Electrochemical performance data

[0065]

[0066] As can be seen from the test results of the various examples and comparative examples in Table 1, the sodium storage performance of the hard carbon material obtained by using the solid-phase crosslinking system of "hydroxyl-containing carbon precursor - isocyanate crosslinking agent - hydroxyl-containing inexpensive carbon source" described in this invention, combined with pre-oxidation at a low heating rate, pre-carbonization in an inert atmosphere, and high-temperature carbonization treatment, is significantly improved. Examples 5-7 used a combination of small molecule diisocyanate and isocyanate polymers, which further improved the electrochemical performance of the hard carbon material. In contrast, the overall electrochemical performance of comparative examples 1 to 3 was lower than that of the examples. Pre-carbonization, the addition of sucrose, and the addition of isocyanate crosslinking agents are all necessary technical means for improving the performance of hard carbon materials in this invention, and none of them can be omitted.

Claims

1. A method for preparing an isocyanate-modified pitch-based hard carbon material, characterized in that, Includes the following steps: (S1) Mix the asphalt, isocyanate crosslinking agent and polysaccharide evenly; (S2) Allow the mixture to stand and react, allowing the isocyanate to react with the hydroxyl groups to obtain the crosslinking precursor; (S3) Pre-oxidize the crosslinking precursor in an oxygen-containing atmosphere; (S4) Pre-carbonize in an inert atmosphere and then carbonize at high temperature to obtain hard carbon material.

2. The preparation method according to claim 1, characterized in that, In step S1, the asphalt is selected from at least one of coal tar pitch and petroleum asphalt, and softened at 60-180℃; the isocyanate crosslinking agent is selected from toluene diisocyanate, diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, triphenylmethane triisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, HDI trimer, IPDI trimer, and polymeric MDI; the polysaccharide is selected from at least one of sucrose, starch, cellulose and its derivatives, chitosan, and dextran.

3. The preparation method according to claim 1, characterized in that, The isocyanate crosslinking agent is a mixture of small molecule diisocyanate and isocyanate polymers; the small molecule diisocyanate is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, triphenylmethane triisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate; the isocyanate polymer is selected from at least one of HDI trimer, IPDI trimer, and polymeric MDI; the polysaccharide is sucrose; Furthermore, the isocyanate crosslinking agent is a mixture of small molecule diisocyanate and isocyanate polymer in a mass ratio of 1-2:

1.

4. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of asphalt, isocyanate crosslinking agent and polysaccharide is 4-6:2-3:1-2.

5. The preparation method according to claim 1, characterized in that, In step S2, the static reaction is allowed to stand at 15-40℃ for 3-6 hours.

6. The preparation method according to claim 1, characterized in that, In step S3, the oxygen-containing atmosphere is oxygen or air, and the pre-oxidation is to raise the temperature to 250-300℃ and hold it for 1-2 hours; the heating rate is 0.1-2℃ / min, preferably 0.5-1℃ / min.

7. The preparation method according to claim 1, characterized in that, In step S4, the inert atmosphere is nitrogen and / or argon, and the pre-carbonization involves heating to 400-500℃, preferably 450℃, and holding for 3-6 hours at a heating rate of 1-20℃ / min, such as 2-5℃ / min; the high-temperature carbonization involves heating to 1000-1400℃ and holding for 4-8 hours.

8. A hard carbon material for sodium-ion batteries, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.

9. The use of the hard carbon material prepared by the preparation method according to any one of claims 1-7 as a negative electrode material for sodium-ion batteries.

10. A sodium-ion battery, wherein the negative electrode comprises a hard carbon material prepared by the preparation method according to any one of claims 1-7.

Citation Information

Patent Citations

  • Asphalt-based hard carbon, preparation method thereof and sodium ion battery negative electrode material

    CN121849911A